PREVALENCE OF POTENTIAL RISK OF FALLS AND INACTIVATION OF THE TRANSVERSUS ABDOMINIS MUSCLE AS A RISK FACTOR IN A COMMUNITY-DWELLING ELDERLY POPULATION - Jogunola, Olabanji Oladele; Aiyegbusi , Ayoola Ibifubara; Okafor , Udoka Arinze; Balogun, Oluwaseyi Jessy; Braimoh , Kolawole Thomas (Journal of Current Research and Review (JCRR), 2024)
Objectives Falls are the leading cause of unintentional injury-related deaths in the elderly; hence, prevention of falls is an important public health issue. There is however a need to evaluate the potential risk of falls and associated predictive risk factors in the elderly. Current evidence has shown that inactivation of the transversus abdominis (TA) results in loss of balance and falls, particularly in the elderly. Thus, this study determined the prevalence of the potential risk of falls and its correlation with inactive TA among selected community-dwelling elderly. Methods This study screened 112 male and female participants aged 65 years and above for the potential risk of falls using the fall prediction tool for the elderly. Seventy-three participants with a high risk of falls were screened using ultrasonography for transversus abdominis muscle activation. All data were summarized and analyzed using descriptive statistics of mean, percentage, and standard deviation. Principal Component Analysis (PCA) was used to determine the association of age, body mass index (BMI), chair stand test (CST), timed up and go test (TUG), four-stage balance test (FSB), and fall prediction tool (FPT) with transversus abdominis activation. Results The prevalence of risk of falls among the participants was 73%. Analysis of principal components to determine the correlation of age, body mass index (BMI), chair stand test (CST), timed up and go (TUG), four-stage balance (FSB), and fall prediction tool (FPT) with the activation of the transversus abdominis showed that FSB had excellent quality representation, whereas CST and FPT had good quality representation. All these had positive correlations with the activation of the transversus abdominis. Conclusion This study identified inactivation of the transversus abdominis as an intrinsic factor for the potential risk of falls in community-dwelling elderly